Happiness dynamics with quarterly life event data - Paul Frijters; David W. Johnston; Michael A. Shields (Institute for the Study of Labor (IZA), 2008)
This paper addresses the question of when and to what extent individuals are affected by major positive and negative life events, including changes in financial situation, marital status, death of child or spouse and being a victim of crime. The key advantage of our data is that we are able to identify these events on a quarterly basis rather than on the yearly basis used by previous studies. We find evidence that life events are not randomly distributed, that individuals to a large extent anticipate major events and that they quickly adapt. These effects have important implications for the calculation of monetary values needed to compensate individuals for life events such as crime or death of spouse. We find that our new valuation methodology that incorporates these dynamic factors produces considerably smaller compensation valuations than those calculated using the standard approach.
urn:nbn:de:101:1-20080723156
Keywords: I0; 330; Life satisfaction; life events; adaptation; compensation; Lebenszufriedenheit; Lebensverlauf; Privater Haushalt; Australien